Prospects For Implementing A Unified Digital Educational Resources And Services Portal: The Case Of Uzbekistan (Eurasian Journal of Engineering and Technology, 2025)
Modern digital technologies are emerging as a crucial factor in enabling innovative approaches and high efficiency in the field of education. From this perspective, the need to integrate all digital educational resources and interactive services into a single information platform is growing day by day. This article provides a comprehensive analysis of the conceptual foundations, practical aspects, and expected outcomes of implementing the “Unified Digital Educational Resources and Services Portal” in Uzbekistan’s education system. Additionally, comparative analyses based on advanced international practices have been conducted, and recommendations are provided to identify promising directions for the effective implementation of the portal, including the introduction of a digital ecosystem in education through a unified portal.